Spectroscopic behaviour of some superconducting materials containing tetraoxoanions - Lavat, A. E. (2001)
A number of materials of composition YSr₂Cu₂.(XO₄)₀.₂Oy(X = S, P, V) and others in which Y (III) was partially replaced by Sr(II) and/or Ca(II) were prepared by solid state reactions. Their unit cell parameters were determined and refined from X-ray powder data. The infrared spectra of the different tetraoxoanions incorporated in these materials were analyzed and discussed in detail. The vibrational modes of the other structural units present in these lattices were also approximately assigned in comparison with known spectral data of related materials.